Emerging Infectious Disease Content in Newspaper Editorials: Public Health Concern or Leadership Issue? - You, Myoungsoon; Joo, Jungmin; Park, Esuri; Noh, Ghee-Young; Ju, Youngkee (Science communication, 2017)
We conducted a content analysis of newspaper editorials on the Middle East respiratory syndrome outbreak in Korea. Subject matter, social and personal efficacy information, and affective tone were evaluated using a mixed-methods approach. An analysis of 241 publications with the acronym “MERS” revealed that public health was the most salient, followed by leadership/governance, coping, medical system, and economic consequences. Societal efficacy information was more frequent than personal efficacy information, and a negative tone was predominant. However, leadership became the most frequent in the later stages. Personal efficacy information decreased over time and across content with a negative tone.